Cyclosporine-A-Induced Intracranial Thrombotic Complications: Systematic Review and Cases Report - Song, Si-ying; Wang, Zhong-ao; Ding, Yu-chuan; Ji, Xun-ming; Meng, Ran (Frontiers in Neurology, 2021)
This study reported two cases of intracranial thrombotic events of aplastic anemia (AA) under therapy with cyclosporine-A (CsA) and reviewed both drug-induced cerebral venous thrombosis (CVT) and CsA-related thrombotic events systematically. We searched PubMed Central (PMC) and EMBASE up to Sep 2019 for publications on drug-induced CVT and Cs-A-induced thrombotic events. Medical subject headings and Emtree headings were used with the following keywords: “cyclosporine-A” and “cerebral venous thrombosis OR cerebral vein thrombosis” and “stroke OR Brain Ischemia OR Brain Infarction OR cerebral infarction OR intracerebral hemorrhage OR intracranial hemorrhage.” We found that CsA might be a significant risk factor in inducing not only CVT but also cerebral arterial thrombosis in patients with AA.